Prospects and challenges of recombinant spider venom enzymes: insights from Loxosceles and Phoneutria venom protease expressions - Dresler, Josephine; Rodriguez, Ivonne; Paas, Anne; Cabrera-Orefice, Alfredo; Vilcinskas, Andreas; Lüddecke, Tim (Frontiers in Bioengineering and Biotechnology, 2025)
Spiders use chemically complex venoms to overpower prey. Such venoms are primarily composed of neurotoxic disulfide-rich peptides, linear peptides, and enzymes. The latter have received little scientific attention thus far, and despite their great translational potential, functional data on spider venom enzymes remain scarce. Hence, a more comprehensive understanding is sought, not only to provide valuable insights into their biological functionality but also to facilitate the development of novel biotechnological applications. However, their chemical isolation is prevented by the minuscule venom yields available from most spiders. Recombinant expression emerged as a promising methodology to overcome these restrictions, but comparatively few efforts have been made to establish technologies for different enzyme families. In particular, few works have explored the pivotally important technical aspects of spider venom enzyme expression, including strain selection, culture conditions, and product purification. In this study, we explore these aspects using two spider venom enzymes as a case study, with particular emphasis on the purification and refolding of an astacin-like metalloprotease from Loxosceles intermedia venom. The enzymes were produced as fusion proteins using diverse Escherichia coli strains to identify the most effective production strains, including their optimal production conditions. Thioredoxin A, a 6x-His-Tag, and a cleavage site for activated factor X allowed efficient purification and subsequent removal of all fusion tags, and we report in detail the purification of the mass spectrometry-confirmed L. intermedia metalloprotease from inclusion bodies. This exploratory study outlines the technical details and potential pitfalls encountered during the development of this production process and provides an important baseline for future attempts to express spider venom enzymes.